2014
DOI: 10.1007/s00296-014-3012-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of dsRNA ligating pattern recognition receptors TLR3, MDA5, and RIG-I. Association with systemic lupus erythematosus and clinical phenotypes

Abstract: This study aimed to demonstrate possible associations between genetic polymorphisms in Toll-like receptor 3, interferon induced with helicase C domain 1 (IFIH1) and DEAD (Asp-Glu-Ala-Asp) box polypeptide 58 and systemic lupus erythematosus (SLE), including the phenotypes lupus nephritis and malar rash, as well as the presence of autoantibodies against nucleic acid-containing complexes. Genotyping was carried out in two Danish cohorts [Copenhagen (CPH) and Odense (ODE)] totaling 344 patients and was compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The updated meta-analysis in our study showed association between rs1990760 and SLE, pointing towards a protective role for the C allele, thus reinforcing previous results by Gateva et al (2009) and Enevold et al (2014). Despite the overall divergent results obtained with rs1990760 in SLE (Figure 2), our meta-analysis indicates either a protective association for the C allele or no association at all.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The updated meta-analysis in our study showed association between rs1990760 and SLE, pointing towards a protective role for the C allele, thus reinforcing previous results by Gateva et al (2009) and Enevold et al (2014). Despite the overall divergent results obtained with rs1990760 in SLE (Figure 2), our meta-analysis indicates either a protective association for the C allele or no association at all.…”
Section: Discussionsupporting
confidence: 68%
“…Despite the overall divergent results obtained with rs1990760 in SLE (Figure 2), our meta-analysis indicates either a protective association for the C allele or no association at all. These differences might be explained by taking into account the heterogeneous genetic background of the populations included in this and other studies, as also proposed by Enevold et al (2014). Sensitivity analysis estimates indicate that a large number of studies are required to produce more robust meta-analysis results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While none of the original studies highlighted a change in this pathway for any of the naive patient samples, Smiljanovic et al (2012) report TLR2 to be up-regulated in their tumor necrosis factor (TNF)-α in vitro-treated lupus monocytes compared to controls [39]. Furthermore, polymorphisms in TLR3, TLR7 and TLR9 genes have been associated with lupus patients in some populations [6062] and a number of in vivo and in vitro studies have strongly implicated a number of TLRs to play a role in the pathogenesis of lupus [58]. By combining the datasets from the individual microarray studies here, we have similarly identified TLR signaling as a key regulatory mechanism that is differentially regulated in the PBMCs from lupus patients when compared to unaffected controls; and have demonstrated consistent differential regulation of TLR3.…”
Section: Discussionmentioning
confidence: 99%